Experimental and numerical investigations of the piezoelectric energy harvesting via friction-induced vibration. (1st September 2018) - Wang, D.W.; Mo, J.L.; Wang, X.F.; Ouyang, H.; Zhou, Z.R.
Highlights: Piezoelectric energy harvesting via friction-induced vibration (FIV) is proposed. A test setup which is able to generate FIV and harvest FIV energy is created. Test results confirms the feasibility of piezoelectric energy harvesting via FIV. The relationship between the working parameters and energy harvesting is studied. Numerical analysis simulates the energy harvesting behaviours via FIV. Abstract: In this work, piezoelectric energy harvesting via friction-induced vibration is investigated experimentally and numerically. A test setup which is able to generate friction-induced vibration and simultaneously harvest vibration energy is created. The experimental results verify the feasibility of energy harvesting via friction-induced vibration. They suggest that there is a critical driving speed for the friction system to generate strongest friction-induced vibration and output highest voltage; a larger normal load is beneficial for producing stronger vibration and outputting higher voltage; the external electric resistance has little effect on the vibration of the friction system, instead it will modify the output voltage amplitude within limits. To further understand the experimental findings, both the complex eigenvalue analysis and implicit dynamic analysis are performed in ABAQUS. The complex eigenvalue analysis further confirms the feasibility of energy harvesting by means of friction-induced vibration, and shows that the vibration in both tangential and normal directions can be harvested. The implicit dynamic analysis verifies the effect of driving speed and normal load on the system dynamics and harvested energy. Accordingly, a two-degree-of-freedom friction system model is proposed to qualitatively characterise the effect of external electric resistance on the system dynamics and harvested energy. This investigation offers quite a new way of harvesting vibration energy.